ANALISIS PENGARUH FAKTOR-FAKTOR FUNDAMENTAL KINERJA BANK DAN MAKRO EKONOMI TERHADAP STABILITAS PERBANKAN DI INDONESIA - Sri Setiawati, Ririt Iriani (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
This study aimed to analyze the influence of fundamental factors and macro-economic performance of the bank to the stability of banks in Indonesia during the period 2011-2017. Fundamental factors indicated by the LDR, NPL and CAR. Meanwhile, macroeconomic factors indicated by variable Bi rate and inflation. Banking stability is reflected by the banking stability index. This study uses a quantitative approach to the panel regression analysis model data by using the tools of the computer program eviews 10. The results of these empirically demonstrated that simultaneous, variable factors of fundamental and macroeconomic factors have a significant influence on the stability of perbankan. While partially, the results of this study indicate that the variable LDR, NPL, Bi rate and inflation significant influence on the stability of the banking and CAR variables not significant effect on the stability of the banking system.